Application of Wood Vinegar for Fungal Disease Controls in Paddy Rice - Wilawan Chuaboon; Nattapone Ponghirantanachoke; Dusit Athinuwat (Applied Environmental Research, 2016)
A survey of an outbreak of fungal diseases of rice variety Phitsanulok2 (PLS91014-16-1-5-1) was conducted in Thailand during June 2014 to January 2015 using a W-random sampling pattern. The study revealed the incidence of several diseases including brown spot (Bipolaris oryzae), narrow brown leaf streak (Cercospora oryzae), and dirty panicle (Alternaria padwickii, C. oryzae, Curvularia lunata, Fusarium semitectum, and B. oryzae). This study evaluated the efficacy of wood vinegar for control of these fungal diseases. A compleel randomized design was used, using the above variety in 3 replications. In the laboratory we found wood vinegar to be effective in inhibiting growth of representative pathogens such as C. lunata, B. oryzae, F. semitectum, and A. padwickii, the causal agent of dirty panicle disease. The field results confirmed the efficacy of wood vinegar under greenhouse conditions, with significantly reduced disease incidence of brown spot and dirty panicle, and significantly enhanced germination, seedling vigor, shoot height, root length, and fresh weight, when compared with the untreated control. However, seed treatment and 6 foliar sprays of wood vinegar under field conditions at Ang Thong showed no significant differences from the conventional treatment in suppression of brown spot, narrow brown leaf streak, and dirty panicle. The result demonstrates a promising alternative approach to control of key rice diseases.